2013
DOI: 10.1371/journal.pone.0071955
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Radiotherapy, Diabetes and Osteoporosis as Risk Factors for Dental Implant Failure: A Meta-Analysis

Abstract: BackgroundThere are conflicting reports as to the association between smoking, radiotherapy, diabetes and osteoporosis and the risk of dental implant failure. We undertook a meta-analysis to evaluate the association between smoking, radiotherapy, diabetes and osteoporosis and the risk of dental implant failure.MethodsA comprehensive research on MEDLINE and EMBASE, up to January 2013, was conducted to identify potential studies. References of relevant studies were also searched. Screening, data extraction and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
161
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(175 citation statements)
references
References 59 publications
9
161
2
3
Order By: Relevance
“…However, several previous studies have demonstrated that smoking reduces the success rate of osseointegration and may be considered to be a risk factor for implant loss. 11,21 Zupnik et al could not find an association between implant failure and smoking, demonstrating a lower OR as well as a p-value of < 0.05. 19 Similarly, many studies have reported maxillary implant placement as a risk factor.…”
Section: Discussionmentioning
confidence: 94%
“…However, several previous studies have demonstrated that smoking reduces the success rate of osseointegration and may be considered to be a risk factor for implant loss. 11,21 Zupnik et al could not find an association between implant failure and smoking, demonstrating a lower OR as well as a p-value of < 0.05. 19 Similarly, many studies have reported maxillary implant placement as a risk factor.…”
Section: Discussionmentioning
confidence: 94%
“…In the last two decades, dental implants have become an increasingly popular procedure, being considered effective and predictable restorations for replacing missing teeth 1,2 . However, although the success and longterm survival of dental implants are well documented in a large number of studies 3 , failures still continue to occur for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…However, although the success and longterm survival of dental implants are well documented in a large number of studies 3 , failures still continue to occur for several reasons. Given the above, risks associated with the failure of dental implants have become a topic widely discussed in recent dental research 2 . A variety of conditions are considered influential in the outcome of the success or failure of dental implants, including: the implant design (length, shape or surface texture), medical risk factors related to the patient (systemic diseases or habits like smoking) and factors related to surgery (experience of the surgeon or surgical planning) 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The literature is divided as to whether advancing age is truly a risk factor for failure. 12,13 It has been suggested that with advancing age, there are changes in bone and collagen that may result in longer healing periods. An important note to make is that older patients may also have more alveolar bone atrophy, resulting in reduced bone volume and increasing the rate of failure.…”
Section: Discussionmentioning
confidence: 99%